Preparation process of positive plate of deep-circulation traction storage battery

By using lead powder, sulfuric acid and additives to prepare positive electrode lead paste and applied to the pretreated positive plate grid, the problem of the powderization of active substances in frequent charge and discharge cycles of the deep cycle traction battery is solved, and the performance of the positive electrode plate of the deep cycle traction battery is reduced in high temperature environment, achieving a longer cycle life and higher charge and discharge efficiency.

CN119905528APending Publication Date: 2025-04-29GUANGDONG OAKLEY GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411908190.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

During the frequent charging and discharging cycles of deep cycles, the active substances are prone to powderization, resulting in degradation of battery performance and prone to sulfateization and high self-discharge rates in high temperature environments.

Method used

The positive electrode lead paste is prepared using lead powder, sulfuric acid and combined additives, and applied to the pretreated positive plate gate to form a stable interface layer, reducing the powdering and separation of active substances and enhancing conductivity.

Benefits of technology

It effectively inhibits the rapid decline in the density of active substances and separation and fall off, extends the cycle life of the battery, improves the charge and discharge efficiency, reduces the self-discharge rate, and enhances the stability of the battery in high-temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a deep-circulation traction storage battery positive plate which comprises a positive plate grid and positive lead plaster, and the positive lead plaster is coated on the surface of the positive plate grid; the positive lead paste is prepared from the following components in parts by weight: 150 to 300 parts of lead powder, 8 to 12 parts of sulfuric acid solution, 0.1 to 0.5 part of antimony trioxide, 0.2 to 0.5 part of stannous mono-sulphate, 2 to 6 parts of red lead, 25 to 50 parts of red lead and 0.05 to 0.15 part of short fiber; the positive plate obtained by the invention can reduce the rapid reduction of the density of the active substance and the separation and falling, and inhibit the rapid attenuation of the discharge capacity of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of storage batteries, and specifically relates to a preparation process of a positive plate of a deep-cycle traction storage battery. Background Art

[0002] Deep Cycle Traction Battery is a battery designed for frequent charge and discharge cycles. It is widely used in electric forklifts, golf carts, electric tour buses, mining equipment and other occasions that require long-term continuous power supply. The positive plate is one of the core components of this battery and directly affects the performance, life and safety of the battery.

[0003] Features and advantages of positive plates include: High cycle life, such as deep cycle capability: The deep cycle traction battery positive plate is specially designed to maintain stable performance during frequent charge and discharge cycles. Compared with ordinary lead-acid batteries, the positive plate of deep cycle batteries has higher resistance to powdering and longer service life. Anti-powdering design: The active material of the positive plate will change in volume during the charge and discharge process, resulting in powdering. By optimizing the formulation of active materials and substrate structure, the positive plate of deep cycle batteries can effectively reduce powdering and extend the cycle life of the battery. High energy density, such as optimized active materials: The deep cycle traction battery positive plate uses high-purity lead dioxide and advanced additive technology to improve the utilization of active materials, thereby increasing the energy density of the battery. This allows the battery to provide more power at the same volume, suitable for equipment that runs for a long time. Efficient conductive network: By optimizing the structure and conductive path of the substrate, the positive plate of the deep cycle battery can achieve faster electron transmission and ion diffusion, improving the battery's charge and discharge efficiency. Good high temperature stability, such as heat resistance: The deep cycle traction battery positive plate is specially treated to maintain stable performance in high temperature environment. High temperature will accelerate the chemical reaction inside the battery, increase the self-discharge rate and corrosion risk. By using high temperature resistant additives and substrate materials, the positive plate of the deep cycle battery can work normally at higher temperatures, reducing the impact of temperature on battery performance. Anti-sulfation: In high temperature environment, the positive plate is prone to sulfation, resulting in a decrease in battery capacity. By optimizing the formulation of active materials and charge and discharge management, the positive plate of the deep cycle battery can effectively inhibit the occurrence of sulfation and extend the service life of the battery. Low self-discharge rate, such as lead-calcium alloy substrate: Using lead-calcium alloy as the substrate material can significantly reduce the self-discharge rate of the battery. Self-discharge refers to the phenomenon that the battery discharges itself when not in use. Excessive self-discharge rate will shorten the storage time and service life of the battery. Lead-calcium alloy substrates have a low self-discharge rate and are suitable for long-term storage and backup power applications.

[0004] Although deep-cycle traction battery positive plates have made significant progress in design and performance, there are still some shortcomings in practical applications. For example, during frequent charge and discharge cycles, the lead dioxide on the positive plate will change in volume, causing the active material to gradually fall off the substrate and form a powdery substance, which is called "powdering"; there are also problems such as sulfation, high self-discharge rate, and performance degradation in high temperature environments, which affect the battery life, efficiency and reliability. Summary of the invention

[0005] The purpose of the present invention is to provide a preparation process of a deep cycle traction battery positive plate, by using lead powder, sulfuric acid and a combined additive to obtain a positive lead paste, and then coating it on a pretreated positive grid, the obtained positive plate can reduce the rapid decrease in active material density and separation and shedding, and inhibit the rapid decay of the battery discharge capacity.

[0006] In order to achieve the above object, the present invention provides the following technical solutions: A deep cycle traction battery positive plate comprises a positive grid and a positive lead paste, wherein the positive lead paste is coated on the surface of the positive grid; the positive lead paste comprises, by weight, 150-300 parts of lead powder, 8-12 parts of sulfuric acid solution, 0.1-0.5 parts of antimony trioxide, 0.2-0.5 parts of stannous sulfate, 2-6 parts of red lead, 25-50 parts of red lead and 0.05-0.15 parts of short fibers.

[0007] Preferably, the mass fraction of the sulfuric acid solution is 15-25%; and the staple fibers are polyester staple fibers.

[0008] Preferably, it also includes 0.5-1 parts of magnesium fluorosilicate solution and 0.02-0.08 parts of graphene composite; the magnesium fluorosilicate solution is prepared by magnesium fluorosilicate crystals and pure water in a mass ratio of 1:1-2; the graphene composite is graphene loaded with iron oxide and cobalt oxide.

[0009] Preferably, the apparent specific gravity of the positive electrode lead paste is 4.5-5.5 g / cm 3 .

[0010] A process for preparing a deep cycle traction battery positive plate comprises the following steps: S1: pre-treat the positive electrode grid for standby use; S2: dry-mixing 150-300 parts of lead powder, 0.1-0.5 parts of antimony trioxide, 0.2-0.5 parts of stannous sulfate, 25-50 parts of red lead, 0.05-0.15 parts of short fibers, and 0.02-0.08 parts of graphene composite to obtain a premix; S3: adding 8-12 parts of sulfuric acid solution and 0.5-1 parts of magnesium fluorosilicate solution to the premix in sequence under stirring to carry out wet mixing reaction to obtain a positive electrode lead paste; S4: coating the dried positive grid with positive lead paste and then curing and drying the plate to obtain a positive green plate; S5: The positive plate is converted into a positive plate for a deep cycle traction battery.

[0011] Preferably, the specific steps of pretreatment in step S1 are: soaking and washing the positive grid in distilled water for 30-60 seconds; and soaking in an ethanol solution with a mass fraction of 30-40% for 20-30 seconds.

[0012] Preferably, the preparation process of the graphene composite in step S2 is: take 15-25 parts of graphene, 2-4 parts of 5-8% by mass ferric chloride aqueous solution, 1-3 parts of 10-15% by mass cobalt chloride aqueous solution and 60-80 parts of ethanol solution, add 1-3 parts of 4-7% by mass sodium hydroxide aqueous solution at a temperature of 60-80°C, stir and react for 40-60 minutes; after filtering and drying, calcine at a temperature of 500-700°C for 5-10 minutes to obtain the graphene composite.

[0013] Preferably, the wet mixing reaction temperature in step S3 is 40-50° C., and the stirring reaction is carried out at a rate of 500-700 r / min for 35-55 min.

[0014] Preferably, the curing and drying step in step S4 is divided into three stages: the first stage drying temperature is 30-40°C, the humidity is ≥90%, and the drying time is 3-4h; the second stage drying temperature is 40-50°C, and the drying time is 7-9h; the third stage drying temperature is 75-85°C, and the drying time is 10-12h.

[0015] Preferably, in step S5, the first constant potential is 1.3-1.4V, charging for 30-40min; the charging circuit is left to stand for 20-30min; the second constant potential is 1.2-1.3V, charging for 30-40min; the charging circuit is left to stand for 20min-30min; the third constant potential is 1.2-1.3V, charging time is 30-40min.

[0016] Antimony trioxide is a white or slightly yellow powder, odorless; melting point is 656℃, density is 5.2 g / cm³ (20℃), almost insoluble in water, but soluble in acid and alkali; stable at room temperature, but easily reacts with reducing agents at high temperature to form metallic antimony or low-valent oxides; usually exists in monoclinic crystal system, but may also form other crystal forms. It is an important inorganic compound, widely used in many industries, especially in flame retardants, glass, ceramics and electronic materials.

[0017] Red Lead, chemically known as lead tetroxide, is a dark red or orange-red powder with a metallic luster. It has a melting point of 500°C and a density of 9.1 g / cm³ (20°C). It is almost insoluble in water, but soluble in acids (such as nitric acid, hydrochloric acid) and alkalis.

[0018] Magnesium fluorosilicate is usually a white or light yellow crystalline powder, sometimes in block form; melting point is about 850°C (decomposition); density: 2.36 g / cm³ (20°C); slightly soluble in water, easily soluble in acids (such as hydrochloric acid and sulfuric acid), insoluble in ethanol; relatively stable at room temperature, but easily decomposed at high temperatures to produce silicon dioxide (SiO2), hydrogen fluoride (HF) and magnesium oxide (MgO); crystal structure: magnesium fluorosilicate belongs to the hexagonal crystal system and has a complex crystal structure, in which silicon atoms and fluorine atoms form a tetrahedral structure, and magnesium ions are located in the gaps between these tetrahedrons.

[0019] Compared with the prior art, the advantages and beneficial effects of the present invention are: The invention prepares positive lead paste from components such as lead powder, sulfuric acid solution, antimony trioxide, stannous sulfate, red lead and short fibers, magnesium fluorosilicate and graphene composites; in the process of charging and discharging, the above components are used to synergistically provide more electron transmission paths, reduce resistance, and thus improve the charging and discharging efficiency of the battery; by adjusting the ion concentration of the electrolyte, the migration of sulfate ions and hydrogen ions is promoted, and the conductivity of the battery is indirectly improved; a stable interface layer is formed to prevent the active material from changing in volume during the charging and discharging process, and further maintain good conductivity; at the same time, the graphene composite forms a three-dimensional conductive network in the positive lead paste, which enhances the electron transfer between the active materials, reduces the problem of uneven local current density, and prevents the active material from pulverizing. DETAILED DESCRIPTION

[0020] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] Example 1 This embodiment provides a process for preparing a deep cycle traction battery positive plate, comprising the following steps: S1: Soak the positive grid in distilled water for 30 seconds and then soak it in 30% ethanol solution for 20 seconds for later use; S2: 15 g of graphene, 2 g of 5% ferric chloride aqueous solution, 1 g of 10% cobalt chloride aqueous solution and 60 g of ethanol solution were mixed, 1 g of 4% sodium hydroxide aqueous solution was added thereto at a temperature of 60°C, and the mixture was stirred at a rate of 500 r / min for 40 min; after filtration and drying, the mixture was calcined at a temperature of 500°C for 5 min to obtain a graphene composite; 150 g of lead powder, 0.1 g of antimony trioxide, 0.2 g of stannous sulfate, 25 g of red lead, 0.05 g of short fibers, and 0.02 g of graphene composite were dry-mixed to obtain a premix; S3: adding 8 g of sulfuric acid solution and 0.5 g of magnesium fluorosilicate solution to the premix in sequence under stirring for wet mixing reaction, at a temperature of 40° C. and a stirring rate of 500 r / min for 35 min to obtain a positive electrode lead paste; S4: After the dried positive grid is coated with positive lead paste, three-stage curing and drying is performed. The first stage is dried at 30°C, 95% humidity, and 3 hours; the second stage is dried at 40°C, and 7 hours; the third stage is dried at 75°C, and 10 hours, to obtain a positive green board; S5: The positive plate is formed, the first constant potential is 1.3V, charging for 30 minutes; the charging circuit is left to stand for 20 minutes; the second constant potential is 1.2V, charging for 30 minutes; the charging circuit is left to stand for 20 minutes; the third constant potential is 1.2V, charging time is 30 minutes; the deep cycle traction battery positive plate is obtained.

[0022] Example 2 This embodiment provides a process for preparing a deep cycle traction battery positive plate, comprising the following steps: S1: Soak the positive grid in distilled water for 60 seconds and then soak it in 40% ethanol solution for 30 seconds for later use; S2: 25 g of graphene, 4 g of 8% ferric chloride aqueous solution, 3 g of 15% cobalt chloride aqueous solution and 80 g of ethanol solution were mixed, 3 g of 7% sodium hydroxide aqueous solution was added thereto at 80°C, and the mixture was stirred at a rate of 600 r / min for 60 min; after filtration and drying, the mixture was calcined at 700°C for 10 min to obtain a graphene composite; 300 g of lead powder, 0.5 g of antimony trioxide, 0.5 g of stannous sulfate, 6 g of red lead, 0.15 g of short fibers, and 0.08 g of graphene composite were dry-mixed to obtain a premix; S3: adding 12 g of sulfuric acid solution and 1 g of magnesium fluorosilicate solution to the premix in sequence under stirring for wet mixing reaction, at a temperature of 50° C. and a stirring rate of 700 r / min for 55 min to obtain a positive electrode lead paste; S4: After the dried positive grid is coated with positive lead paste, three-stage curing and drying is performed. The first stage is dried at 40°C, the humidity is 95%, and the drying time is 4h; the second stage is dried at 50°C, the drying time is 9h; the third stage is dried at 85°C, the drying time is 12h, and a positive green board is obtained; S5: The positive plate is formed, the first constant potential is 1.4V, charging for 40 minutes; the charging circuit is left to stand for 30 minutes; the second constant potential is 1.3V, charging for 40 minutes; the charging circuit is left to stand for 30 minutes; the third constant potential is 1.3V, charging time is 40 minutes; the deep cycle traction battery positive plate is obtained.

[0023] Example 3 This embodiment provides a process for preparing a deep cycle traction battery positive plate, comprising the following steps: S1: Soak the positive grid in distilled water for 50 seconds and then soak it in 35% ethanol solution for 26 seconds for later use; S2: 22g of graphene, 3g of 7% ferric chloride aqueous solution, 2g of 12% cobalt chloride aqueous solution and 70g of ethanol solution were mixed, 2g of 5% sodium hydroxide aqueous solution was added at 70°C, and the mixture was stirred at a rate of 600r / min for 55min; after filtration and drying, the mixture was calcined at 600°C for 8min to obtain a graphene composite; 200 g of lead powder, 0.3 g of antimony trioxide, 0.4 g of stannous sulfate, 4 g of red lead, 0.1 g of short fiber, and 0.06 g of graphene composite were dry-mixed to obtain a premix; S3: adding 10 g of sulfuric acid solution and 0.8 g of magnesium fluorosilicate solution to the premix in sequence under stirring for wet mixing reaction, at a temperature of 45° C. and a stirring rate of 600 r / min for 45 min to obtain a positive electrode lead paste; S4: After the dried positive grid is coated with positive lead paste, three-stage curing and drying is performed. The first stage is dried at 35°C, the humidity is 95%, and the drying time is 3.5h; the second stage is dried at 45°C, the drying time is 8h; the third stage is dried at 80°C, the drying time is 11h, and a positive green board is obtained; S5: The positive plate is subjected to chemical reaction, the first constant potential is 1.35V, charging for 35 minutes; the charging circuit is left to stand for 25 minutes; the second constant potential is 1.25V, charging for 35 minutes; the charging circuit is left to stand for 25 minutes; the third constant potential is 1.25V, charging time is 35 minutes; the deep cycle traction battery positive plate is obtained.

[0024] Comparative Example 1 The difference from Example 1 is that step S2 does not contain the graphene composite, and the other steps remain unchanged.

[0025] Comparative Example 2 The difference from Example 1 is that step S2 does not contain an aqueous solution of ferric chloride, and the other steps remain unchanged.

[0026] Comparative Example 3 The difference from Example 1 is that step S3 does not contain magnesium fluorosilicate solution, and the other steps remain unchanged.

[0027] Comparative Example 4 The difference from Example 1 is that in step S4, drying is performed once at a drying temperature of 75° C., and the other steps remain unchanged.

[0028] Performance Test: The positive plates prepared in the embodiments and comparative examples were matched with negative plates to make lead-acid battery model 6-DZF-22 finished batteries. Battery performance test: Under a laboratory environment of 25±2℃, 4 assembled battery packs were sampled, and the battery packs were discharged at IC211.0A to a termination voltage of 1.75V / cell, and the discharge time was recorded and the actual discharge capacity of the battery was calculated. The results are shown in the following table.

[0029] Table 1

[0030] From the above performance test results, it can be seen that the positive plates prepared in Examples 1-3 have good performance. In particular, Example 3 has better comprehensive performance. However, since Comparative Examples 1-4 do not adopt the necessary technical solutions, their corresponding performance tests are significantly worse than those of the Examples. The above experimental results further prove the importance of the technical solutions defined in the present invention for its technical effects.

[0031] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A deep cycle traction battery positive plate, characterized in that: It comprises a positive electrode grid and a positive electrode lead paste, wherein the positive electrode lead paste is coated on the surface of the positive electrode grid; in parts by weight, the positive electrode lead paste comprises 150-300 parts of lead powder, 8-12 parts of sulfuric acid solution, 0.1-0.5 parts of antimony trioxide, 0.2-0.5 parts of stannous sulfate, 2-6 parts of red lead, 25-50 parts of red lead and 0.05-0.15 parts of short fibers.

2. A deep cycle traction battery positive plate according to claim 1, characterized in that: The mass fraction of the sulfuric acid solution is 15-25%; the short fibers are polyester short fibers.

3. A deep cycle traction battery positive plate according to claim 1, characterized in that: It also includes 0.5-1 parts of magnesium fluorosilicate solution and 0.02-0.08 parts of graphene composite; the magnesium fluorosilicate solution is prepared by magnesium fluorosilicate crystals and pure water in a mass ratio of 1:1-2; the graphene composite is graphene loaded with iron oxide and cobalt oxide.

4. A deep cycle traction battery positive plate according to claim 1, characterized in that: The apparent specific gravity of the positive electrode lead paste is 4.5-5.5 g / cm 3 .

5. A process for preparing a positive plate of a deep cycle traction battery, characterized in that: The steps include: S1: pre-treat the positive electrode grid for standby use; S2: dry-mixing 150-300 parts of lead powder, 0.1-0.5 parts of antimony trioxide, 0.2-0.5 parts of stannous sulfate, 25-50 parts of red lead, 0.05-0.15 parts of short fibers, and 0.02-0.08 parts of graphene composite to obtain a premix; S3: adding 8-12 parts of sulfuric acid solution and 0.5-1 parts of magnesium fluorosilicate solution to the premix in sequence under stirring to carry out wet mixing reaction to obtain a positive electrode lead paste; S4: coating the dried positive grid with positive lead paste and then curing and drying the plate to obtain a positive green plate; S5: The positive plate is converted into a positive plate for a deep cycle traction battery.

6. The process for preparing a deep cycle traction battery positive plate according to claim 5, characterized in that: The specific steps of pretreatment in step S1 are: soaking and washing the positive grid in distilled water for 30-60 seconds; soaking in an ethanol solution with a mass fraction of 30-40% for 20-30 seconds.

7. The process for preparing a deep cycle traction battery positive plate according to claim 5, characterized in that: The preparation process of the graphene composite in step S2 is: take 15-25 parts of graphene, 2-4 parts of 5-8% by mass ferric chloride aqueous solution, 1-3 parts of 10-15% by mass cobalt chloride aqueous solution and 60-80 parts of ethanol solution, add 1-3 parts of 4-7% by mass sodium hydroxide aqueous solution at a temperature of 60-80°C, stir and react for 40-60 minutes; after filtering and drying, calcine at a temperature of 500-700°C for 5-10 minutes to obtain a graphene composite.

8. The process for preparing a deep cycle traction battery positive plate according to claim 5, characterized in that: The wet mixing reaction in step S3 is carried out at a temperature of 40-50° C. and stirred at a rate of 500-700 r / min for 35-55 min.

9. The process for preparing a deep cycle traction battery positive plate according to claim 5, characterized in that: The curing and drying step in step S4 is divided into three stages: the first stage is a drying temperature of 30-40°C, a humidity of ≥90%, and a drying time of 3-4h; the second stage is a drying temperature of 40-50°C, and a drying time of 7-9h; the third stage is a drying temperature of 75-85°C, and a drying time of 10-12h.

10. The process for preparing a deep cycle traction battery positive plate according to claim 5, characterized in that: In step S5, the first constant potential is 1.3-1.4V, charging for 30-40min; the charging circuit is left to stand for 20-30min; the second constant potential is 1.2-1.3V, charging for 30-40min; the charging circuit is left to stand for 20min-30min; the third constant potential is 1.2-1.3V, charging time is 30-40min.